2015
DOI: 10.2147/phmt.s66730
|View full text |Cite
|
Sign up to set email alerts
|

Links and risks associated with adenotonsillectomy and obesity

Abstract: Adenotonsillectomy (A&T) is a very common surgical procedure in children. Over the past 20 years the principal indication for A&T in children has changed from recurrent adenotonsillitis to obstructive sleep apnea. The physiopathology of obstructive sleep apnea syndrome (OSAS) is multifactorial and obesity has been shown to be one of the main factors correlated with its occurrence. On the other hand, the prevalence and severity of childhood obesity have become a veritable epidemic problem in the past 30 years. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
0
2
0
2
Order By: Relevance
“…At a follow-up appointment, children with recurrent tonsillitis more frequently underwent an A&T rather than an adenoidectomy [18]. Recurrent tonsillitis can serve as an indication for tonsillectomy based on specific criteria outlined by medical guidelines [33]. Finally, a reduced percentage of children with a history of recurrent otitis media and hearing loss had persistent SDB after adenoidectomy surgery [14].…”
Section: Discussionmentioning
confidence: 99%
“…At a follow-up appointment, children with recurrent tonsillitis more frequently underwent an A&T rather than an adenoidectomy [18]. Recurrent tonsillitis can serve as an indication for tonsillectomy based on specific criteria outlined by medical guidelines [33]. Finally, a reduced percentage of children with a history of recurrent otitis media and hearing loss had persistent SDB after adenoidectomy surgery [14].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, evidence has shown that adenotonsillectomy does not cause obesity or weight gain. On the contrary, studies have proven that it is effective in reducing obstructive symptoms in obese children and improving their quality of life [ 23 ]. Chronic neglected adenotonsillitis has been associated with serious complications, such as pulmonary hypertension, cor pulmonale, and heart failure [ 24 ], with other studies showing an association between gastroesophageal reflux disease and recurrent adenotonsillitis [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…МЕТОДИЧЕСКИЕ РЕКОМЕНДАЦИИ летальность в возрасте [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]…”
unclassified
“…Особенности периоперационного периода при ОСА и синдроме гиповентиляции [27]: ÿ повышенная чувствительность к снотворным и седативным препаратам, а также опиоидам; ÿ вероятность трудной масочной вентиляции и трудной интубации; ÿ вероятность быстрой десатурации при индукции анестезии; ÿ вероятность гиперкапнии во время анестезии.ň Рекомендация 5. У пациентов с ожирением рекомендуется оценка трудных дыхательных путей[28][29][30][31] (УДД -2, УУР -А).…”
unclassified